Opinions and strategies of Australian health professionals on tackling cancer‐related financial toxicity: A nationwide survey. Issue 1 (19th May 2022) - Gordon, Louisa G.; Nabukalu, Doreen; Chan, Raymond J.; Goldsbury, David E.; Hobbs, Kim; Hunt, Lee; Karikios, Deme J.; Mackay, Gillian; Muir, Laura; Leigh, Lillian; Thamm, Carla; Lindsay, Daniel; et al.
Abstract: Aim: To understand the opinions and current practices of health professionals on the topic of addressing cancer‐related financial toxicity among patients. Methods: A cross‐sectional online survey was distributed through Australian clinical oncology professional organizations/networks. The multidisciplinary Clinical Oncology Society of Australia Financial Toxicity Working Group developed 25 questions relating to the frequency and comfort levels of patient–clinician discussions, opinions about their role, strategies used, and barriers to providing solutions for patients. Descriptive statistics were used and subgroup analyses were undertaken by occupational groups. Results: Two hundred and seventy‐seven health professionals completed the survey. The majority were female ( n  = 213, 77%), worked in public facilities (200, 72%), and treated patients with varied cancer types across all of Australia. Most participants agreed that it was appropriate in their clinical role to discuss financial concerns and 231 (88%) believed that these discussions were an important part of high‐quality care. However, 73 (28%) stated that they did not have the appropriate information on support services or resources to facilitate such conversations, differing by occupation group; 7 (11%) social workers, 34 (44%) medical specialists, 18 (25%) nurses, and 14 (27%) of other occupations. Hindrances to discussing financial concerns were insufficient resources or support systems to refer to, followed by lack of time in a typical consultation. Conclusion: Health professionals in cancer care commonly address the financial concerns of their patients but attitudes differed across occupations about their role, and frustrations were raised about available solutions. Resources supporting financial‐related discussions for all health professionals are urgently needed to advance action in this field. Abstract : Many health professionals caring for patients with cancer often discuss the financial concerns of their patients and have increasing awareness of these issues but are limited by time and practical supports. Resources supporting financial‐related discussions for all health professionals are urgently needed to advance action in this field.